The Political Economy of the World Bank : The Early Years - Alacevich, Michele (Stanford: Stanford University Press and the World Bank, 2013)
This book covers the early years of the International Bank of Reconstruction and Development (IBRD), commonly known as the World Bank when it first confronted the issue of development as a fundamental part of its mission. The book is mainly concerned with how the Bank interpreted its mission and, more specifically, how its mission was born: what events shaped it, what cultural and ideological background influenced it and what was the historical context in which it arose. So this book is a contribution to the study of the prehistory of development, understood in its social and economic context. In this respect, the study of the early years of the World Bank offers excellent context for observation for three reasons. First, during its history there is a clear separation between the growth phase and the phase of social objectives. Second, in the first years of activity already the Bank could hear murmurs of opposition. Finally, there was a sudden change in the mandate of the institution changed from supporting the reconstruction of Europe after the war, to help developing countries. The transition from one phase to another was a formative one and redefined the institution. The upshot of the foregoing was to set a fertile ground for exploring the signs of conflict between the different approaches to development. The first chapter deals with the historiography that underlies the writing. It refers to a wide literature using periods of transition or crisis in the history of the institution to understand its dynamics and mechanisms. Reducing its support for European reconstruction, the Bank focused on the development of countries. The internal tensions that arose and led to a complete break between the Bank and the director of the mission (the economist Lauchlin Currie) are very useful for understanding better the evolution of the institution. The third chapter explores the tensions between Currie and the Bank and particularly, between Currie and the economist Albert Hirschman, who the Bank replaced as envoy to Colombia. The final chapter focuses again on the International Bank and particularly in lending mechanisms for developing countries.